Polycrystalline diamond material with double-peak structure and preparation method thereof

By preparing polycrystalline diamond materials with bimodal structures, the toughness of the material is improved by using composite structures with different grain sizes, the brittleness of diamond materials is solved, the combination of high hardness and high toughness is achieved, and the industrial application of diamond materials is broadened.

CN119390066APending Publication Date: 2025-02-07NINGBO UNIV
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202411459607.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-18
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The brittleness of diamond materials causes them to easily break or break in impact loads or high stress environments, limiting their industrial applications.

Method used

By preparing polycrystalline diamond materials with bimodal structures, the toughness of the material is improved by using composite structures of different grain sizes. The material consists of nano-onion carbon and micrographite, and is prepared by mechanical grinding and high-temperature and high-pressure synthesis technology to form a bimodal structure of nano-diamond and micro-diamond.

Benefits of technology

While maintaining high hardness, polycrystalline diamond materials have significantly improved their fracture toughness. The hardness is close to single crystals and their toughness is more than twice as high. It is suitable for environments where impact loads or high stresses are required.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119390066A_ABST
    Figure CN119390066A_ABST
Patent Text Reader

Abstract

The invention provides a polycrystalline diamond material with a double-peak structure and a preparation method of the polycrystalline diamond material, and relates to the technical field of superhard materials. The polycrystalline diamond material comprises the following raw materials: nano onion carbon and micron graphite, and the preparation method comprises the following steps: weighing the nano onion carbon and the micron graphite, carrying out mechanical grinding treatment, fully mixing to obtain mixed powder, pressing the mixed powder with a mold, and wrapping with boron nitride to obtain a green body; and the blank is loaded into a high-temperature and high-pressure synthesis cavity for high-temperature and high-pressure synthesis treatment, then heat preservation and pressure maintaining treatment is carried out, cooling and pressure relief treatment are carried out, and the polycrystalline diamond material with the double-peak structure is obtained. According to the method disclosed by the invention, the grain size with a'double-peak structure 'is constructed in the polycrystalline diamond, so that the fracture toughness of the polycrystalline diamond is improved by more than two times while high hardness is maintained, the extremely-hard and high-toughness polycrystalline diamond is successfully synthesized, and a reference is provided for toughening of other ceramic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of superhard materials, and in particular to a polycrystalline diamond material with a double-peak structure and a preparation method thereof. Background Art

[0002] Diamond, which is a tetrahedral structure formed by carbon atoms connected by strong covalent bonds, is the hardest material in nature, with a Vickers hardness of 80~120GPa. Due to its unique physical and chemical properties, it is widely used in industrial fields, especially in cutting, grinding and drilling. Whether it is used to manufacture high-precision cutting tools or for drilling in the mining and construction industries, the high hardness of diamond can effectively improve work efficiency and processing quality. In addition, diamond also has good thermal conductivity and chemical stability, which makes it show a wide range of application potential in many fields such as electromagnetism, optics and semiconductors.

[0003] However, diamond has a significant disadvantage, namely, poor toughness. When subjected to strong impact or excessive pressure, diamond is prone to cracking or breaking, resulting in tool damage and production stagnation, which seriously reduces its service life and limits its industrial application, especially in environments that need to withstand impact loads or high stress. Therefore, how to overcome the brittleness of diamond and improve its toughness is a problem that needs to be solved urgently.

[0004] In order to solve this problem, researchers have conducted a lot of research to explore ways to improve the toughness of diamond. For example, the toughness of diamond can be improved to a certain extent by preparing composite materials by doping metal or ceramic materials, but the hardness of diamond products will be seriously reduced (HV≈40GPa). In addition, nano-polycrystalline diamond prepared by catalyst-free phase change of graphite has about double the toughness of single crystal, but it still cannot meet the requirements of industrial applications. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the present invention provides a method for preparing a polycrystalline diamond composite of two different grain sizes, and utilizes the "double peak structure" of the grain size to increase the toughness of the polycrystalline diamond. This invention not only broadens the path for the application of diamond materials, but also provides a reference for the development of other high-performance materials.

[0006] The invention provides a polycrystalline diamond material with a double-peak structure. The raw material composition of the polycrystalline diamond material comprises nano-onion carbon and micron graphite, wherein the molar percentage of the nano-onion carbon is 10-90 mol%, the particle size of the nano-onion carbon is 50 nm, and the particle size of the micron graphite is 40-60 μm.

[0007] The present invention obtains a polycrystalline diamond material with a bimodal structure by mixing carbon raw materials with different grain sizes, wherein nano-onion carbon is a special carbon nanostructure, which is formed by stacking multiple carbon nanoshells and looks like an onion. Its special structure transforms into nano-diamond under high pressure and can form microstructures such as twin boundaries and stacking faults, which is beneficial to improving the hardness of diamond; and martensitic phase transformation occurs in the process of micron graphite phase transformation into diamond to form larger diamond particles. Different grain sizes make the material show excellent performance at different size levels, thereby obtaining a polycrystalline diamond material with extremely high hardness and extremely high toughness.

[0008] In some embodiments, the polycrystalline diamond material has a Vickers hardness of 153.6-169 GPa and a toughness of 14.0-15.2 MPa·m 0.5 .

[0009] The second object of the present invention is to provide a method for preparing a polycrystalline diamond material having a bimodal structure, the preparation method specifically comprising the following steps: S1, weighing nano-onion carbon and micron graphite, grinding them mechanically and mixing them thoroughly to obtain a mixed powder, pressing the mixed powder with a mold and then wrapping it with boron nitride to obtain a green body; S2, loading the green body obtained in step S1 into a high temperature and high pressure synthesis cavity for high temperature and high pressure synthesis, and performing heat preservation and pressure preservation treatment; S3, subjecting the sample after heat preservation and pressure preservation in step S2 to cooling and pressure relief treatment to obtain a polycrystalline diamond material with a double peak structure.

[0010] Compared with the prior art, the present invention first ensures that nano-onion carbon and micron graphite are fully mixed through mechanical grinding treatment, thereby improving the uniformity inside the material. Boron nitride is wrapped around the mixed powder after pressing, which can play an isolation role in the high-temperature and high-pressure synthesis process to prevent other impurities from entering the material and affecting its purity and performance. The subsequent high-temperature and high-pressure synthesis technology can realize the transformation of carbon materials into diamonds in a short time, greatly shortening the production cycle and improving production efficiency. The integrity of the transformation process is ensured through heat preservation and pressure treatment, which is conducive to obtaining a more uniform and stable polycrystalline structure.

[0011] In some embodiments, in step S1, the nano-onion carbon is further pretreated before mechanical grinding, and the specific steps of the pretreatment are as follows: maintaining at 900° C. for 1 hour in an environment with flowing argon gas.

[0012] Compared with the prior art, the present invention pre-treats the nano-onion carbon, which has the following main effects: high-temperature treatment can effectively remove organic matter and other impurities on the surface of the nano-onion carbon, and improve its purity, which is very important for subsequent high-temperature and high-pressure synthesis, because any impurities may affect the performance of the final product; at the same time, the high-temperature treatment can also activate the surface of the nano-onion carbon, making it easier to combine with micron graphite, so as to achieve a better dispersion effect in the subsequent mixing process; finally, the mixing effect is optimized: the pre-treated nano-onion carbon is easier to be evenly mixed with other components, so as to ensure the uniformity and consistency of the final product.

[0013] In some embodiments, in step S2, during the high temperature and high pressure synthesis process, LaCrO3 is used as the insulation material, metal Re is used as the heating body, pyrophyllite is used as the assembly sealing material, MgO or ZrO2 is used as the pressure transmission medium, and a W-Re thermocouple is used for synchronous temperature measurement.

[0014] Compared with the prior art, the present invention adopts the above raw materials in the following ways: LaCrO3 (lanthanum chromate) is a good high-temperature insulating material, which can maintain good thermal stability and mechanical strength at high temperatures, and is helpful to maintain uniform temperature in the synthesis cavity; metal rhenium (Re) has an extremely high melting point (about 3180°C), and has good electrical conductivity and thermal conductivity at high temperatures, and is very suitable for use as a heating element; pyrophyllite is a natural mineral with good heat resistance and sealing properties, and can play a good role in pressure transmission and sealing under high temperature and high pressure environments; magnesium oxide (MgO) or zirconium oxide (ZrO2) is used as a pressure transmission medium, which can transmit pressure under high temperature and high pressure environments while maintaining good thermal stability and mechanical strength; tungsten-rhenium (W-Re) thermocouple is a temperature measuring element that can withstand extremely high temperatures, and is suitable for temperature measurement during high temperature and high pressure synthesis processes. The use of W-Re thermocouples for synchronous temperature measurement can monitor temperature changes during the synthesis process in real time, ensure the accuracy of temperature control, and thus improve product quality.

[0015] In some embodiments, in step S2, the parameters of the high temperature and high pressure synthesis process are as follows: the synthesis temperature is 1800° C., and the synthesis pressure is 15 GPa.

[0016] Compared with the prior art, the present invention limits the synthesis parameters of high temperature and high pressure to the above temperature and pressure conditions because: 1800°C is higher than the lower temperature limit of the phase transition of graphite to diamond, which can make nano-onion carbon and micron graphite phase transition to diamond phase under high pressure environment. The pressure of 15GPa belongs to the high pressure range commonly used in high temperature and high pressure synthesis technology, under which graphite can phase transition to diamond.

[0017] In some embodiments, in step S2, the parameters of the heat preservation and pressure preservation treatment are as follows: the heat preservation time is 15 minutes, and the pressure preservation time is 200 minutes.

[0018] Compared with the prior art, the present invention adopts the above-mentioned heat preservation and pressure holding time, and the setting of the heat preservation time and pressure holding time is to ensure that the material can be fully transformed and form the required structure under high temperature and high pressure conditions. Under such conditions, nano-onion carbon and micron graphite can fully phase change without rapid growth to form polycrystalline diamond with a bimodal structure. At the same time, a longer pressure holding time helps to improve the uniformity of the material and the stability of the experiment.

[0019] In some embodiments, in step S3, the specific steps of cooling and decompression treatment are: naturally cooling the heated sample to room temperature at a rate of 100°C / min and then decompressing it. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 This is the X-ray diffraction spectrum of the "double peak structure" polycrystalline diamond material obtained in Example 1 of the present invention; Figure 2 This is the X-ray diffraction spectrum of the "double peak structure" polycrystalline diamond material obtained in Example 2 of the present invention; Figure 3 This is the X-ray diffraction spectrum of the "double peak structure" polycrystalline diamond material obtained in Example 3 of the present invention; Figure 4 This is the X-ray diffraction spectrum of the "double peak structure" polycrystalline diamond material obtained in Example 4 of the present invention; Figure 5 This is an indentation image of the "double peak structure" polycrystalline diamond material prepared in Example 4 of the present invention; Figure 6 This is the X-ray diffraction spectrum of the “double-peak structure” polycrystalline diamond material obtained in Example 5 of the present invention. DETAILED DESCRIPTION

[0021] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0022] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0023] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.

[0024] The technical effects of the present invention are described below in conjunction with specific embodiments.

[0025] Example 1 S1: 10 mol% nano-onion carbon powder and 90 mol% micron graphite powder were mechanically ground for 2 h and fully mixed, the particle size of the nano-onion carbon was 50 nm, the particle size of the micron graphite was 50 μm, and they were pressed into a cylinder with a diameter of 2 mm and a height of 2 mm by a mold, and then wrapped with boron nitride. The nano-onion carbon was also pretreated before mechanical grinding, and the specific steps of the pretreatment were as follows: in an environment with flowing argon, kept at 900 ° C for 1 h; S2: putting the raw material wrapped in step S1 into a high-temperature and high-pressure synthesis assembly, using LaCrO3 as a heat-insulating material, metal Re as a heating body, pyrophyllite as a sealing material for the assembly, MgO or ZrO2 as a pressure-transmitting medium, and using a W-Re thermocouple for synchronous temperature measurement, under the conditions of a synthesis pressure of 15 GPa and a synthesis temperature of 1800°C, keeping the temperature for 15 min and keeping the pressure for 200 min, and then cooling to room temperature at a rate of 100°C / min; S3: After the sample is cooled to room temperature, the pressure is released.

[0026] The X-ray diffraction spectrum of the polycrystalline diamond material prepared in this embodiment is shown in Figure 1 ;from Figure 1 It can be seen that the main component of the sample is cubic diamond, including nano-diamond grains transformed from nano-onion carbon phase and micro-diamond grains transformed from micro-graphite phase, and the two grain size distributions have a "double peak structure". The sample has good toughness and hardness close to that of single crystal.

[0027] After testing, the Vickers hardness of the "double peak structure" polycrystalline diamond prepared in this embodiment is 109.7 GPa, and the toughness is 10.45 MPa·m 1 / 2 .

[0028] Example 2 This embodiment provides a polycrystalline diamond material, which is different from Embodiment 1 only in that the raw material components of this embodiment are: 30 mol% nano-onion carbon powder and 70 mol% micron graphite powder, and the rest are the same as Embodiment 1 and will not be repeated here.

[0029] The X-ray diffraction spectrum of the polycrystalline diamond material prepared in this embodiment is shown in Figure 2 .from Figure 2 It can be seen that by increasing the proportion of nano-onion carbon and the proportion of nano-grains in polycrystalline diamond, the hardness of the sample is increased, while the toughness remains unchanged.

[0030] After testing, the Vickers hardness of the "double peak structure" polycrystalline diamond prepared in this embodiment is 115.4GPa, and the toughness is 10.9MPa·m 1 / 2 Example 3 This embodiment provides a polycrystalline diamond material, which is different from Embodiment 1 only in that the raw material components of this embodiment are: 50 mol% nano-onion carbon powder and 50 mol% micron graphite powder, and the rest are the same as Embodiment 1 and will not be repeated here.

[0031] The X-ray diffraction spectrum of the polycrystalline diamond material prepared in this embodiment is shown in Figure 3 .from Figure 3 It can be seen that as the proportion of nano-onion carbon continues to increase, the hardness value of the sample increases significantly, which is significantly higher than single crystal diamond.

[0032] After testing, the Vickers hardness of the bimodal polycrystalline diamond prepared in this embodiment is 150.3 GPa and the toughness is 9.7 MPa·m 1 / 2 Example 4 This embodiment provides a polycrystalline diamond material, which is different from Embodiment 1 only in that the raw material components of this embodiment are: 70 mol% nano-onion carbon powder and 30 mol% micron graphite powder, and the rest are the same as Embodiment 1 and will not be repeated here.

[0033] The X-ray diffraction spectrum of the polycrystalline diamond material prepared in this embodiment is shown in Figure 4 , indentation diagram see Figure 5 ;from Figure 4 and Figure 5 It can be seen that with the increase of nano-onion carbon, the number of nanoparticles in polycrystalline diamond increases, the hardness of the sample increases by about 30% compared with the single crystal, the toughness increases by about two times, and the distribution ratio of the two grains in the "double peak structure" reaches the best.

[0034] After testing, the Vickers hardness of the bimodal polycrystalline diamond prepared in this embodiment is 161.3 GPa, and the toughness is 14.6 MPa·m 1 / 2 Example 5 This embodiment provides a polycrystalline diamond material, which is different from Embodiment 1 only in that the raw material components of this embodiment are: 90 mol% nano-onion carbon powder and 10 mol% micron graphite powder, and the rest are the same as Embodiment 1 and will not be repeated here.

[0035] The X-ray diffraction spectrum of the polycrystalline diamond material prepared in this embodiment is shown in Figure 6 .from Figure 6 It can be seen that when there are too many nanocrystals, the effect of the "double peak structure" in the sample is weakened, and the toughness of the sample is significantly reduced, approaching that of a single crystal.

[0036] After testing, the Vickers hardness of the bimodal polycrystalline diamond prepared in this embodiment is 128.4 GPa and the toughness is 4.5 MPa·m 1 / 2 .

[0037] From the above results, it can be seen that the method of the present invention constructs a grain size with a "double peak structure" in polycrystalline diamond, so that the fracture toughness of polycrystalline diamond is increased by more than two times while maintaining high hardness, and successfully synthesizes extremely hard and tough polycrystalline diamond (HV=161.3±7.7 GPa, K IC =14.6±0.6 MPa·m 0.5 ), and provides a reference for toughening other ceramic materials.

[0038] It is worth mentioning that the experiments involved in the above embodiments were completed on a Kawai type 6-8 press (1000 t) 10-5 experimental assembly.

[0039] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed in the present application should be included in the protection scope of the present application. Therefore, the protection scope of the present application shall be based on the protection scope of the claims.

Claims

1. A polycrystalline diamond material having a bimodal structure, characterized in that: The raw material composition of the polycrystalline diamond material includes nano-onion carbon and micron graphite, and the molar percentage of the nano-onion carbon is 10-90 mol%, the particle size of the nano-onion carbon is 50 nm, and the particle size of the micron graphite is 40-60 μm.

2. The polycrystalline diamond material with a bimodal structure according to claim 1, characterized in that: The polycrystalline diamond material has a Vickers hardness of 153.6-169 GPa and a toughness of 14.0-15.2 MPa·m 0.5 .

3. A method for preparing a polycrystalline diamond material having a bimodal structure according to claim 1 or 2, characterized in that: The preparation method specifically comprises the following steps: S1, weighing nano-onion carbon and micron graphite, grinding them mechanically and mixing them thoroughly to obtain a mixed powder, pressing the mixed powder with a mold and then wrapping it with boron nitride to obtain a green body; S2, loading the green body obtained in step S1 into a high temperature and high pressure synthesis cavity for high temperature and high pressure synthesis, and performing heat preservation and pressure preservation treatment; S3. After the sample has been kept warm and pressurized, it is cooled and depressurized to obtain a polycrystalline diamond material with a double-peak structure.

4. The method for preparing a polycrystalline diamond material having a bimodal structure according to claim 3, characterized in that: In the step S1, the nano-onion carbon is pretreated before mechanical grinding, and the specific steps of the pretreatment are as follows: maintaining at 900° C. for 1 hour in an environment with flowing argon gas.

5. The method for preparing a polycrystalline diamond material having a bimodal structure according to claim 3, characterized in that: In step S2, during the high temperature and high pressure synthesis process, LaCrO3 is used as the heat insulation material, metal Re is used as the heating body, pyrophyllite is used as the sealing material for assembly, MgO or ZrO2 is used as the pressure transmission medium, and a W-Re thermocouple is used for synchronous temperature measurement.

6. The method for preparing a polycrystalline diamond material having a bimodal structure according to claim 3, characterized in that: In step S2, the parameters of the high temperature and high pressure synthesis process are as follows: the synthesis temperature is 1800° C., and the synthesis pressure is 15 GPa.

7. The method for preparing a polycrystalline diamond material having a bimodal structure according to claim 3, characterized in that: In step S2, the parameters of the heat preservation and pressure preservation treatment are as follows: the heat preservation time is 15 minutes, and the pressure preservation time is 200 minutes.

8. The method for preparing a polycrystalline diamond material having a bimodal structure according to claim 3, characterized in that: In step S3, the specific steps of cooling and decompression treatment are: naturally cooling the heated sample to room temperature at a speed of 100°C / min and then decompressing it.

Citation Information

Cited By

  • Micro-nano polycrystalline diamond composite material and preparation method thereof

    CN121850666A

  • Cubic boron nitride-nano polycrystalline diamond composite material and preparation method thereof

    CN121872777A

  • Hexagonal boron nitride-nano polycrystalline diamond composite material and preparation method thereof

    CN121974695A